Pengaruh Pembelajaran Matematika Terintegrasi Islam Terhadap Pembentukan Karakter Siswa - Nada Aviola; Shyfatul Hayati; Windi Pebria; Annisa Annisa; M. Imamuddin (Universitas Pahlawan Tuanku Tambusai, 2023)
Mathematics is one of the sciences that has an important role in education. Mathematics education also contains character values in it. Among the character values are discipline, honesty, hard work, creativity, curiosity, independence, communicative and responsibility. So that by learning mathematics can also form the character of students. So in this paper the author conducted a study on “the influence of Islamic integrated mathematics learning on the formation of Student character